Unraveling the Status Quo of Decentralized Autonomous Organizations - Barbosa, Alexandre Pires; Wegner, Douglas; Santos, Rodrigo Pereira dos (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2026: Anais do XXII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2026.248638, 2026)
Research Context: Decentralized Autonomous Organizations (DAO) emerge as innovative structures operating on blockchain infrastructures, providing transparency, decentralization, and autonomy in digital governance and coordination processes. Scientific and/or Practical Problem: Despite their transformative potential, DAO face significant obstacles, such as scalability limitations, risks of power concentration, legal ambiguities, and complex incentive models. Proposed Solution and/or Analysis: This study investigates recent scientific literature on DAO, seeking to understand their current state, focusing on how they have been conceptualized, characterized, evaluated, and applied. Related IS Theory: The research draws on the wisdom of crowd theory, which explains how collective decision-making can overcome individual choices, and sociotechnical theory, which emphasizes the interaction between technological infrastructures and social structures. Together, these perspectives frame DAO as hybrid systems that integrate algorithmic processes with collective human governance. Research Method: A systematic mapping study was conducted, encompassing the collection, selection, and coding of 47 primary studies published in relevant scientific sources. Summary of Results: The results highlight the conceptual consensus on the decentralized and smart contract-based nature of DAO, propose categories of structural challenges, and map recurring application domains, such as decentralized finance (DeFi), open science, energy, and digital art. Furthermore, the results demonstrate the transition of DAO from algorithmic entities to sociotechnical hybrids, connected to emerging trends such as the metaverse, NFTs, and decentralized artificial intelligence. Contributions and Impact to IS area: This study provides an updated theoretical foundation for the IS area, mapping the state of the art of DAO, identifying structural challenges, and emphasizing their evolution toward hybrid models. Most importantly, it reveals the complexity and originality of uniting the three main pillars of information systems (code, governance, and automated processes), thus contributing to the design of more resilient, inclusive, and sustainable digital governance systems in emerging decentralized ecosystems.